SOMATOTYPES DISTRIBUTION FEATURES IN HEALTHY AND PATIENTS WITH MYOPIA BOYS AND GIRLS, RURAL RESIDENTS PODILLIA REGION OF UKRAINE - Kryvovyaz, S.O. (World of Medicine and Biology, 2015)
Aim of our work – set features of somatotypes distribution in healthy and patients with myopia boys and girls of the second period of childhood, rural residents Podilsk region of Ukraine. Materials and methods From data bank of scientific and research center Vinnitsa National Medical University named after Pirogov taken initial anthropometric and somatotypological indicators of practically healthy and patients with myopia girls and boys period of the second childhood (63 healthy and 46 patients with myopia boys aged from 9 to 12 years and 54 healthy and 49 patients with myopia girls aged from 9 to 11 years) that in the third generation living in rural areas in the territory of Podilsky region of Ukraine. Anthropometric survey of adolescents conducted in accordance with the scheme of V.V. Bunak. Definition of somatotype by method J. Carter and B. Heath. Definition component composition of body weight carried by techniques J. Matiegka. Statistical data processing was performed using licensed software package «Statistica 6.1» using parametric and nonparametric methods for assessing the results. Results. Discussions Found that in patients girls percentage of endomorph was significantly larger and ectomorph - significantly lower than in healthy girls. When comparing the percentage of somatotypes between healthy and sick boy significant differences or trends difference value of the indicator is not set. Found that in healthy boys significantly greater percentage of ecto-mesomorph and mesomorph compared with healthy girls. In healthy girls percentage of eсtomorph and intermediate middle somatotype was significantly greater than in healthy boys. In patients girls set significantly (p